Lifeworld and Social Space. Spatial Restructuring and Urban Governance in Berlin. - Falahat, Somaiyeh; Madanipour, Ali (Taylor & Francis, 2020)
To direct analysing, monitoring, planning, and administrating the city, a new ‘lifeworld’ system has divided Berlin into spatial units, while an overarching strategy of ‘social space’ has become a new paradigm for the city. The paper critically examines these two concepts, with a reference to two urban programmes: ‘Neighbourhood Management’ and ‘District Centres’, as different institutional arrangements which aim at socio-spatial improvements within designated areas. It asks if the application of these philosophical and sociological concepts in Berlin indicate an alternative, more democratic approach, going beyond the common hierarchical, functionalist and bureaucratic methods of spatial subdivision. It shows a realignment of the spatial, social and institutional dimensions of the city, as a new basis for a more integrated system of urban information and governance, in a move from engineering approaches towards a heightened sensitivity to the social context. However, it argues, there are theoretical tensions between the phenomenological roots of these concepts and the delimitation of space into managed units. It asks whether the administrative and technocratic logics remain, recalibrating the map of governance around a new spatial framework, while increasing pressures on deprived neighbourhoods for self-reliance.
Keywords: Stadtentwicklung; Sozialraum; Soziale Stadt; Quartiersmanagement; Lebenswelt; Stadtteilarbeit; Stadtmanagement; Planungsraum; Planungstheorie; Urban Governance